Pelatihan Pembuatan Media Pembelajaran Berbasis Powerpoint Interaktif Guru Pondok Tahfidz Ahlul Jannah Paddinging Sanrobone - Abdul Wahab; Muh Aidil Sudarmono; Abdul Qahar Zainal; Muh Azhar; Junaedi (CV. Multi Kreasi Media, 2023)
One of the teacher competencies that has not been implemented properly is skills in teaching activities, namely Making Interactive Powerpoint-Based Learning Media for teachers. This difficulty is caused because teachers lack the ability to make learning media. Therefore, it is necessary to hold training activities on Making Interactive Powerpoint-Based Learning Media for teachers of Pondok Tahfidz Ahlul Jannah Paddinging. Through this training activity, teacher competence in Making Interactive Powerpoint-Based Learning Media is expected to increase. Based on the situation analysis, the problems formulated: 1) The implementation of learning, is felt to be less attractive to students and tends to be boring, 2) Teacher motivation to carry out learning implementation innovations is very low, 3) The knowledge of teachers in designing and using interactive power point-based learning media. The training was conducted for 1 day face-to-face, by inviting 15 teachers of Pondok Tahfidz Ahlul Jannah, with a frequency of 3 visits. The outputs include: increasing teacher competence in the field of Interactive Powerpoint-Based Learning Media.